Does Population Size Drive Changes in Transatlantic Vagrancy for Gulls? A Study of Seven North Atlantic Species - Acosta Alamo, Marlen; Manne, Lisa L.; Veit, Richard R. (Frontiers in Ecology and Evolution, 2022)
European gulls Chroicocephalus ridibundus, Larus canus and L. graellsii have dispersed to North America and C. ridibundus and L. graellsii have bred or attempted to breed. North American gulls L. delawarensis, Leucophaeus atricilla, Leucophaeus pipixcan and Chroicocephalus philadelphia have dispersed to Europe, although no successful breeding by non-hybrid pairs has yet occurred. We hypothesized that as gull population sizes increase, the number of birds exploring potential new breeding sites also increases. To test our hypothesis, we compared the number of transatlantic vagrants to the population size on the previous year using generalized linear models. We found an increasing number of transatlantic vagrants moving in both directions, which suggests that vagrancy is not a random phenomenon driven by strong winds nor caused by reverse migration. Population size predicted transatlantic vagrancy in four of the seven species. However, our hypothesis that increases in population size drive increases in vagrancy was only supported in two of these instances. We further looked at sub-populations of L. delawarensis in North America and tested our hypothesis for each subpopulation. We found partial support for our hypothesis for these data. Even within one species, we observed multiple relationships between vagrancy and population size. Our results showed that size or trend in source population size - in some circumstances - is clearly a driver of vagrancy, but other factors must play an important role too. As anthropogenic development continues, and high-quality habitats become farther apart, it is important that we continue to investigate all drivers of vagrancy because the persistence of a species may depend crucially on its longest-distance dispersers.